STUDI EKSPERIMEN SUPLAI GENERATOR OXYHYDROGEN MENGGUNAKAN KATALIS KOH - Prasetya, Hendrik Elvian Gayuh; Pratilastiarso, Joke; Amalia, Rif'ah; F, Mardatillah Intan (P3M Politeknik Negeri Indramayu, 2019)
Oxyhydrogen is the most promising gas which significantly can reduce the fuel consumption and the number of emissions that produced, by adding the gas into combustion chamber. To utilize decreasing emissions, this paper study about added oxyhydrogens gas on combustion process (hybrid) in motor fuel. This paper focuses on evaluating the performance (power, mass flow, and efficiency) of oxyhydrogen generator with 12V source voltage, while for the generator installation circuit is done in parallel which is expected to produce maximum oxhydrogen gas content. The type of electrolyte used as a generator solution is a base ???????????? concentrate (1, 3, 5, 7, 9 gram / Li ter), basic solution ???????????? is chosen because it has a tendenc to produce a lot of hydrogen gas. The methods are design the generator, string the generator and the measuring instrument up, and also the performance testing. As the result, the higher consentrate of the catalyst, the higher the power needed, the higher mass flow produced, and the higher efficiency that obtained by using parallel electrode aligntment.